HERMENEUTIKA M. Ë‹Ä€BED AL-JÄ€BIRÄª DAN IMPLIKASINYA TERHADAP HUKUM ISLAM: (Kasus Nasakh dan Nikah MutË‹ah) - Mohamad Yahya (AS-SALAM, 2012)
Al-JÄbirÄ«â€™s hermeneutics and its implications for Islamic law is topic of this article. Framework thinking of al-JÄbirÄ«â€™s hermeneutics was constructed on the basis of two principles, al-faá¹£l and al-waá¹£l. Al-faá¹£l principle was applied by using three approaches; structural analysis, historical criticism, and ideological criticism, while the principle of al-waá¹£l using mathematical-intuition approach. He had applied that methodological construction in the interpretation of the Qurâ€™an, as the source of all sources of Islamic law. The implication is reconstruction, and even deconstruction, of various theories and themes of Islamic law. Theoretically, one of which is about nasakh. For him, no nasakh in the Qurâ€™an, except humanâ€™s understanding about law is changed. While thematically, one of which is mutË‹ah. As a consequence of the absence nasakh in the Qur'an, for him mutË‹ah remain in force if the condition and the situation requires.